Flame retardancy study of recycled polymeric foam filled composite building material / Syed Anas Syed Mustafa, Rahmah Mohamed and Lily Soraya Amerudin - Syed Mustafa, Syed Anas; Mohamed, Rahmah; Amerudin, Lily Soraya (2015)
Flame retardancy is an important fire safety element often emphasized by the construction sectors; It is utilized to prevent material ignition, and thus limit the effects of building fires. The preparation and characterization of Unsaturated Polyester Resin (UPR) composite systems filled with recycled Expanded Polystyrene (EPS) were systematically investigated. Core additives such as Flame Retardant (FR) and Antioxidant (AO) were added to the composite for imparting suitable characteristics to the composite. The result obtained via the comparison of the various composite systems studied had revealed that certain additives imparts higher flame retardancy levels than others, but each type of additives might had interacted with the polymeric matrixes differently. Thus, it could be concluded that the varying use of additives affects the systems' flame retardancy and thermal properties. Further in depth studies of the polymeric composite may help in determining and confirming the actual mechanisms which these additives produces the effect on material's flammability.